THE EFFECT OF SUBCULTURE ON HAIRY ROOT DEVELOPMENT OF JAVA GINSENG (Talinum paniculatumGaertn.) - Yachya, Arif (Fakultas Sains dan Teknologi Universitas Airlangga, 2011)
Java ginseng (Talinum paniculatum Gaertn.)root was reported to have efficacy similar to the Korean ginseng(Panax ginseng)root. Hairy root induction of Java ginseng on free hormone solid medium Murashige and Skoog (MS) using genetic transformation mediated by Agrobacterium rhizogenes had succesfully performed. 2 -3 cm in lenght of hairy roots were initiated from cut edge of leaves after two weeks incubation and were used for subculture experiments on solid and liquid MS medium without hormone. Subculture swere performed 4 times for two weeks period. Final incubation of the fourth subculture showeddifferences of medium type (solid and liqiud) affected hairy root development. Hairy rootson solid MS medium grew straight and had no brancing, whereas hairy roots on liquid medium hadbranching and forming ball like structures (2-3 structures/cm). Hairy root swhich were subcultured on liquid medium looked thicker than on solid medium. The thickness of hairy root, branching and formation ball like structure indicated suitability liquid medium as subculture medium than solid medium.